Application of automatic statistical post-processing method for analysis of ultrasonic and digital dermatoscopy images. Issue 1 (1st January 2018) - Drulyte, Indre; Ruzgas, Tomas; Raisutis, Renaldas; Valiukeviciene, Skaidra; Linkeviciute, Gintare
ABSTRACT: Ultrasonic and digital dermatoscopy diagnostic methods are used in order to estimate the changes of structure, as well as to non-invasively measure the changes of parameters of lesions of human tissue. These days, it is very actual to perform the quantitative analysis of medical data, which allows to achieve the reliable early-stage diagnosis of lesions and help to save more lives. The proposed automatic statistical post-processing method based on integration of ultrasonic and digital dermatoscopy measurements is intended to estimate the parameters of malignant tumours, measure spatial dimensions (e.g. thickness) and shape, and perform faster diagnostics by increasing the accuracy of tumours differentiation. It leads to optimization of time-consuming analysis procedures of medical images and could be used as a reliable decision support tool in the field of dermatology.